Variation of height integrated eastward current intensity of the equatorial electrojet during solar maximum and minimum years (2012)
Variation of the height integrated eastward current intensity of the equatorial electrojet was examined in the solar maximum years (1991 and 2002) and solar minimum years (1995 and 2006) respectively using CHAMP satellite data. Data were selected from the hours of 10 to 13 around local noon and during magnetically quiet periods when the Equatorial electrojet was expected to be strongest. Daily averages over all longitudes were used to obtain mean monthly variation. Mean monthly variations in all the seasons were averaged to obtain the mean seasonal variations. The mean monthly and mean seasonal variabilities were also obtained using standard methods. Daily variability exists in the eastward current intensity both in the solar maximum and solar minimum years. The magnitude of the mean monthly eastward current intensity is higher in the solar maximum than in the solar minimum. The eastward current intensity is highest during the equinoctial months than other months in both solar maximum and solar minimum years.